Abdominal Pain in Young Adults - O. V. Gaus; M. A. Livzan; D. V. Turchaninov; T. I. Ivanova; D. V. Popello (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A study of abdominal pain incidence in young adults in relation to dietary habits and psychological profile for advancement of health-promoting technologies.Materials and methods. An anonymous quiz survey covered 3,634 students enrolled at Omsk State Medical University in higher and secondary vocational education programmes via online use of the GSRS and WHO CINDI programme questionnaires to assess eating patterns and dietary preferences, as well as a brief multifactor personality inventory scale. Respondents with abdominal pain were divided into subcohorts by pain severity according to GSRS scores (mild, moderate or severe pain).Results. Abdominal pain was reported by 2,300 (63.29%) respondents, of whom 1,243 (54.0%) rated symptoms as mild, 996 (43.3%) and 61 (2.7%) — as moderate to severe. Abdominal pain complaints were more frequent in women (2I = 33.96, p <0.001), but gender had no effect on pain intensity. Pain associated with abdominal bloating and distention (57.65%), gastroesophageal reflux symptoms (38.75%), constipation (30.54%) or diarrhoea (28.4%). The presence and severity of abdominal pain was distinctive of individuals spending the most of average monthly income on food purchase and those actively consuming tea, coffee, added sugar, extra salt in cooked food, while having low intake of fruit and vegetables. A typical personality in severe abdominal pain is hypothymic depressive, hypochondriac in moderate and psychasthenic in mild pain.Conclusion. Abdominal pain is common among medical students predominating in females, associates with the eating pattern, dietary habits and psychological profile.